The Concept of Values in the Lithuanian Worldview - Smetonienė, Irena (Vilnius University Open Series, 2020)
Although the value system has been discussed since the antiquity, the list of underlying values has not been available yet. Socrates elaborated on virtue, courage and justice, Plato was concerned about truth, goodness, wisdom, determination and temperance. Aristotle analysed ethical norms. Thomas Aquinas considered values to be perfection, which exists as absolute good. He distinguished prudence, justice, volitional morality, faith, hope and love. Jeanas-Jacquesas Rousseau tended to exalt ideas of liberty, equality, fraternity, and humanism and considered happiness, reason, sympathy to be underlying values, encouraged development of volition, independence and pro-activeness. The most relevant values for Immanuel Kant included reason, liberty, self-respect, honour, duty, autonomy, volition and goodness. The philosophers of the 20th century, for example, Max Scheler, made attempts to classify values. The Italian philosopher Battista Mondina stated that values can be of different levels (from the perspective of values not all the things and behaviour patterns are equal: some of them possess more value, whereas the others – less) and comprise a certain hierarchy. He presents a more detailed classification of values, which better complies with life and attitudes of an individual in the 20th century. In the end of the 20th century the researchers got an idea of creating a hierarchy of values relevant to a separate nation. The description of the project “Polish Axiological Dictionary”, which distinguishes the values of importance to the Polish, can be considered an example. It is obvious that a unified conception of values did not exist: different authors treated values in a different way. The concept value is used in various meanings: as an aspect of world value, as attractive objects, life quality, valuable things or phenomena, behaviour norms which influence decisions. Values reflect what is most valuable for an individual from cultural, psychological, sociological, moral and esthetical perspectives. An individual is governed and guided by values; he/she lives for them. The values make up the core of every culture. However, the issue of values raises many questions. Firstly, does a canon of universal values exist? In fact, such values as motherland, patriotism, democracy and tolerance are important but are they equally important? Such daily life values as – work, career, and money – are conceptualised. The question arises if this has always and everywhere been like this? Are such values as family, marriage, child still relevant these days? Most likely for Lithuanians these values will hardly differ from common European or common human values but it is still interesting what is typical only of Lithuanians, what did they include into their value system adopting experience of neighbouring countries and what presupposed the meaning of words. Working on the book “Values in the Worldview of Lithuanians” an idea came to mind that following the concept analysis, attempts can be made to classify Lithuanian values. Various classification principles can be applied: • Societal values: state, nation, motherland, language, freedom, land, work, commitment, justice, duty, honour, morality, the good, the beautiful, morals, etc. • Personal values: happiness, family, home, personal liberty, health, loves, etc. They can also be related to the individual’s growth: • Values that build up the personality: home, family, nature, faith, work, morals, love – that is, everything, what a person gets in the family. • Values that improve the personality: state, nation, language, freedom, patriotism, empathy, tolerance, wisdom, etc. – that is, everything, what a person gets at school and in his/her further life. However, strict boundaries do not exist and cannot exist because a person functions as a member of society as well as a separate individual.